2016
DOI: 10.1504/ijttc.2016.081635
|View full text |Cite
|
Sign up to set email alerts
|

User innovation in public service broadcasts: creating public value by media entrepreneurship

Abstract: This research aims to understand how public service media can encourage media entrepreneurship in the society to enrich user innovations as a source of ideas, products, contents, talent and creativity. The assumption is that media entrepreneurs turn users into sources of external creativity and develop user innovations into professional content. This study follows a qualitative approach with a document study of Denmark's public service broadcast and two interviews. Findings indicate that the commitment to qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…Present article suggests that imitative innovation is one of the most important drivers of media entrepreneurship, by showing an opportunity of value delivery in a market with low risk and investment. Khajeheian and Tadayoni (2016) explained another aspect of media entrepreneurs: their advantage in the contract. Their study on public service broadcast showed that large media companies do not outsource the production to the users or small media firms, mainly for the reason of distrust on delivery of professional quality.…”
Section: Ad-ministermentioning
confidence: 99%
See 1 more Smart Citation
“…Present article suggests that imitative innovation is one of the most important drivers of media entrepreneurship, by showing an opportunity of value delivery in a market with low risk and investment. Khajeheian and Tadayoni (2016) explained another aspect of media entrepreneurs: their advantage in the contract. Their study on public service broadcast showed that large media companies do not outsource the production to the users or small media firms, mainly for the reason of distrust on delivery of professional quality.…”
Section: Ad-ministermentioning
confidence: 99%
“…Such media enterprises commission the contract to the smaller enterprises. The advantage of large companies is in their resource and operations; the advantage of small enterprises is innovation (Eliasson and Eliasson, 2005); and the advantage of medium size enterprises is their ability to produce contracts (Khajeheian and Tadayoni, 2016). As Baumol (2002) expressed, most revolutionary new ideas have been provided preponderantly by independent innovators and it is very likely to be continued in the future.…”
Section: Ad-ministermentioning
confidence: 99%
“…Since foreign companies have great financial and experiential resources, technical power, and freedom in investing their resources, they wield great competitive power; therefore, if internal insurance companies fail to prepare and achieve sustainable competitive advantages, they would be unable to survive in this competitive marketplace (Mazloomi & Dadvand, 2011). In today's fast-changing business environment, innovation is a perquisite of retaining competition (Khajeheian and Tadayoni, 2016). Innovation is not simply the incorporation of new technologies into new products or services, but in many cases it involves finding new models of doing business in the face of change and opens up new opportunities (Khajeheian, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Innovation is a fundamental factor in the creation of new ventures (Khajeheian, 2013) and it allows existing companies to survive in competitive markets (Khajeheian, 2016;Khajeheian and Tadayoni, 2016). The more innovative a product/service is, the more complexity and the less risk of imitation by rivals there will be (Emami and Dimov, 2016).…”
Section: Introductionmentioning
confidence: 99%